ANALISIS YURIDIS PEMBATALAN ALAS HAK ATAS TANAH YANG TUMPANG TINDIH (OVERLAPPING) DI KABUPATEN TAPANULI TENGAH (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 652 K/PDT/2016) - SONNY KURNIAWAN (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Syafruddin Kalo2. Muhammad Yamin3. Hasim Purba The research used juridical normative and descriptive analytic method.Secondarydata were gathered by conducting library research and analyzed by usingqualitative data, and the conclusion was drawn deductively. The conclusion isthat the causes of the overlapping legal standing of land in the society arepsychological factor, in which people do not understand the legal aspect of landso that they do not register their land, the weakness in registering their land, theweakness in the regulation of registering their land, incomplete digital map, lackof coordination in surveying and land registering, ignorance in surveying andissuing land certificate, and lad mafia. The efforts made by BPN in forestall it isby improving the performance by controlling administration and coordinationbetween the sections and the village management, and recording registeredcertificatesinto digital maps. The people should participate actively in protectingtheir land by maintaining and installing boundary markers on their land andrecording any legal acts on their land.Keywords: Land, Revocation, Legal Standing, Overlapping